2021
DOI: 10.1038/s41598-020-80167-7
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous shape effect of nanosized helium bubble on the elastic field in irradiated tungsten

Abstract: Bubble pressure and elastic response in helium-irradiated tungsten are systematically investigated in this study. An anomalous shape effect is found that the radial normal stress and mean stress distributions around a nanosized void or bubble are far from the spherical symmetry, which is ascribed to polyhedral geometry characteristic of the nanosized bubble and physical mechanism transition from crystal surfaces dominated to the surface ledges and triple junctions dominated. Molecular simulation shows that You… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…A change of the total energy of the system depends on the shape and volume of the bubble, gas pressure and surface energy [54,55]. At equilibrium, the surface energy of a bubble is compensated by its internal pressure [56]. Thus, the reduction of the total energy of the system would lead to a development of low-energy facets in preference to a spherical shape which has a higher energy.…”
Section: Shape Of Helium Bubbles and Surface Holesmentioning
confidence: 99%
“…A change of the total energy of the system depends on the shape and volume of the bubble, gas pressure and surface energy [54,55]. At equilibrium, the surface energy of a bubble is compensated by its internal pressure [56]. Thus, the reduction of the total energy of the system would lead to a development of low-energy facets in preference to a spherical shape which has a higher energy.…”
Section: Shape Of Helium Bubbles and Surface Holesmentioning
confidence: 99%
“…These properties significantly impact the microstructural evolutions in irradiated materials and provide essential input for multiscale models of microstructural evolutions. For example, previous atomistic simulations in tungsten have shown that bubbles with a high ratio of He to vacancies (He/V ratio) tend to punch out dislocation loops to release the internal pressure of the bubble, which causes local structural changes [12,[19][20][21]. However, considering the different plastic properties of tungsten and beryllium, the release of bubbles' internal pressure in beryllium could be much different, and it is therefore necessary to examine whether similar or different plasticity mechanisms occur in beryllium.…”
Section: Introductionmentioning
confidence: 99%
“…Different from the traditional void structure, He bubbles exhibit more complex microstructure effects due to their internal pressure [25,26]. It was proved that He bubbles with different He/vacancy ratios (R He/V ) will induce heterogeneous stress fields in the materials [27,28], especially, the formation of stacking fault octahedron (SFO) due to the expansion of high-pressurized He bubbles was observed both in experiments [29] and simulations [30,31]. Previous studies have demonstrated He bubbles with different R He/V show different resistance to dislocations [32].…”
Section: Introductionmentioning
confidence: 99%